Determinan Keputusan Pekerja Mandiri menjadi Peserta Jaminan Kesehatan Nasional - Jumatra Laila; Asmaripa Ainy; Dian Safriantini (Disease Prevention and Public Health Journal, 2020)
Background: National health insurance is mandatory for all Indonesians. In Ogan Ilir Regency, the lowest percentage (24,14%) of its participants in December 2016 was found in Indralaya Utara Sub-district, and self-employed participants in this sub-district were only 6,99%. This study aimed to analyze the determinants of the self-employed’s decision to become national health insurance participants in Indralaya Utara Sub-district. Method: This was a cross-sectional study. The population was self-employed in Indralaya Utara Sub-district. The sample was 108 respondents who were selected using cluster sampling and consecutive sampling techniques. Data analysis was conducted by univariate and bivariate with chi-square statistical test. Results: The results illustrated that 18,52% of respondents decided to become national health insurance participants. Variables with p-value<0,005 were: knowledge about national health insurance (p-value=0,011), trust (p-value=0.000), perception about national health insurance (p-value=0,000), attitude (p-value=0,000), income (p-value=0,002), family support (p-value=0,005). Variables with p-value≥0,005 were: education (p-value=0,234), perception about health facilities (p-value=0,162), distance to health facilities (p-value=0,355), health workers support (p-value=0,112). Conclusion: In conclusion, percentage of self-employed who decided become national health insurance participants was still small. Associated factors to the decision of self-employed as participants were: knowledge about national health insurance, trust, perception about national health insurance, attitude, income and family support. It is suggested that the Social Security Administrative Body for Health should routinely conduct socialization on national health insurance to improve the percentage of its participation for self-employed and the benefits of national health insurance could be felt by the entire community.